ChemInform Abstract: Synthesis of 2‐Amino‐3‐cyano‐4H‐chromen‐4‐ylphosphonates and Their Anticancer Properties. Issue 37 (16th September 2014) - Kalla, Reddi Mohan Naidu; Choi, Jin‐Seok; Yoo, Jin‐Wook; Byeon, Seong Jin; Heo, Min Seon; Kim, Il
Abstract A highly efficient and environmentally friendly procedure for the synthesis of title compounds (IV) (12 examples) via a multi‐component reaction using dibutylamine as non‐toxic organocatalyst is developed.